Flow of physiological fluids in microchannels: the sedimentation effect - Garcia, Valdemar (2010)
Microfluidic devices are becoming one of the most promising new tools for diagnostic applications and treatment of several chronic diseases. Hence, it is increasingly important to investigate the rheological behaviour of physiological fluids in microchannels. The main purpose of the present experimental work is to investigate the flow of two different physiological fluids frequently used in microfluidic devices. The working fluids were physiological saline (PS) and dextran 40 (Dx40) containing about 6% of sheep red blood cells (RBCs), respectively. The capillaries were placed horizontally on a slide glass and the flow rate of the working fluids was kept constant by using a syringe pump. By means of a camera the images were taken and transferred to the computer to be analysed. Generally, the results show that PS and Dx40 have different flow behaviour due to the sedimentation of the RBCs.